2020
DOI: 10.1038/s41598-020-63721-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of topical nitroglycerin in the prevention of mastectomy flap necrosis: a systematic review and meta-analysis

Abstract: Flap necrosis is a common complication after mastectomy, and nitroglycerin (NTG) ointment has been used successfully to treat it. However, it is not clear whether topical NTG can completely prevent the occurrence of flap necrosis after breast cancer surgery, and it is also unclear whether this treatment may cause side effects. Three randomized controlled trials (RCTs) and two retrospective cohort studies (RCSs) were included in our investigation. This meta-analysis was conducted in accordance with the Preferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Our review also showed the potential for nitroglycerin to increase flap survival while decreasing skin flap necrosis. These results are similar to previous studies looking at nitroglycerin on skin flaps, including a meta-analysis by Wang and colleagues 65 that reveals a reduction in rates of flap necrosis. Finally, in keeping with the large body of anesthesia literature, 66 we found that nerve blocks were an effective approach to reducing postoperative pain.…”
Section: Discussionsupporting
confidence: 91%
“…Our review also showed the potential for nitroglycerin to increase flap survival while decreasing skin flap necrosis. These results are similar to previous studies looking at nitroglycerin on skin flaps, including a meta-analysis by Wang and colleagues 65 that reveals a reduction in rates of flap necrosis. Finally, in keeping with the large body of anesthesia literature, 66 we found that nerve blocks were an effective approach to reducing postoperative pain.…”
Section: Discussionsupporting
confidence: 91%
“…Topical NTG has been well studied in the prevention of mastectomy flap necrosis, with a recent meta-analysis showing that NTG significantly improved rates of full-thickness flap necrosis over placebo, but did not prevent superficial flap necrosis (ie, congestion). 4 The studies included in that meta-analysis tested NTG as a preventative measure administered to all patients following mastectomy, not as an intervention for threatened flaps. Dent et al studied the use of NTG in the treatment of 65 cases of NAC ischemia following nipple-sparing mastectomy, reporting a 100% or 71% salvage rate for partial-thickness or full-thickness ischemia, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Nitroglycerin effectively causes vasodilatation by releasing nitric oxide leading to vascular smooth muscle relaxation and increased tissue perfusion with a main action on the veins, hence increasing the salvage response of the skin flaps 35 , 36 . Another known desirable effect is that nitroglycerin exerts an antithrombotic action 37 .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that nitroglycerin ointment has a potent local vasodilator effect and increases the local blood flow that could potentially improve flap survival, although it is not popularly used for preventing skin flap necrosis, possibly due to the lack of effect shown in some studies 6 , 7 . However, others have shown desirable results on flap survival in both humans and animals 8 10 .…”
Section: Introductionmentioning
confidence: 99%